(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The article discusses current trends in the development of digital marketing in the field of services and tourism, in particular the theoretical and methodological foundations of the concept of digital marketing, development strategies and practice of use in the field of tourism and services. The experience of foreign countries and current trends in the development of global trends in the field of digitalization, as well as the role of tourism enterprises in the online travel market, have been studied.